The global dynamics of diabetes and tuberculosis: the impact of migration and policy implications - Girardi, Enrico; Sañé Schepisi, Monica; Goletti, Delia; Bates, Matthew; Mwaba, Peter; Yeboah-Manu, Dorothy; Ntoumi, Francine; Palmieri, Fabrizio; Maeurer, Markus; Zumla, Alimuddin; Ippolito, Giuseppe (International journal of infectious diseases, 2017)
•The convergence of diabetes and tuberculosis is a public health challenge.•Migration may add complexity to the efforts to control tuberculosis and diabetes.•The prevalence of diabetes may be higher in migrants than in native persons with tuberculosis.•Among diabetics, the risk of tuberculosis may be higher in migrants than in native persons.•Interventions are needed to control diabetes-associated tuberculosis in migrants. The convergence between tuberculosis (TB) and diabetes mellitus (DM) will represent a major public health challenge in the near future. DM increases the risk of developing TB by two to three times and also increases the risk of TB treatment failure, relapse, and death. The global prevalence of DM is predicted to rise significantly in the next two decades, particularly in some of the low- and middle-income countries with the highest TB burden. Migration may add further complexity to the effort to control the impact on TB of the growing DM pandemic. Migration may increase the risk of DM, although the magnitude of this association varies according to country of origin and ethnic group, due to genetic factors and lifestyle differences. Migrants with TB may have an increased prevalence of DM compared to the native population, and the risk of TB among persons with DM may be higher in migrants than in autochthonous populations. Screening for DM among migrants, screening migrants with DM for active and latent TB, and improving access to DM care, could contribute to mitigate the effects of DM on TB.